Electroretinographic assessment and diagnostic reappraisal of children with visual dysfunction: A prospective study - Vedantham Vasumathy; Jethani Jithendra; Vijayalakshmi Perumalsamy (Indian Journal of Ophthalmology, 2007)
Purpose: To assess the presence or absence of a retinal cause of visual impairment using electroretinography (ERG) in children with no obvious discernable cause on ocular examination. Design: Prospective observational case series. Materials and Methods: A prospective study was carried out involving 120 children with the mean age 4.4±3.2 years with visual dysfunction. All children underwent ERG under general anesthesia using a special handheld mini-Ganzfeld (Kurbisfeld) dome. Results: Fifty-two (43.3%) children were male and 68 (56.7%) were female. The clinical diagnosis was as follows: Leber′s congenital amaurosis (LCA) (n=47), achromatopsia (n=25), congenital stationary night blindness (CSNB) (n=9) and others (unclassifiable, n=39). The visual acuity ranged from perception of light (PL) to PL with projection in children with LCA. In the rest (n=73), some sort of visually guided behavior was discernable. Following ERG, a diagnostic reappraisal resulted as follows: LCA (n=49), achromatopsia (n=28), CSNB (n=4), cone-rod dystrophy (n=22), rod-cone degeneration (n=7), normal (n=8) and others (unclassifiable, n=2). Except for the two unclassifiable cases, ERG was successful in the diagnosis or exclusion of retinal dysfunction in the rest. By Pearson Chi-square test, there was a statistically significant association between the clinical and ERG diagnosis ( P < 0.001). Conclusion: LCA was the commonest cause of visual dysfunction in our series. A statistically significant correlation between clinical and electrophysiological diagnosis was seen. ERG helped in firmly establishing the presence or absence of global retinal dysfunction in the majority (118/120) of pediatric patients with visual dysfunction.